Perfusion CT in hyperacute cerebral hemorrhage within 3 hours after symptom onset: is there an early perihemorrhagic penumbra? - Herweh, Christian; Jüttler, Eric; Schellinger, Peter; Klotz, Ernst; Schramm, Peter (Journal of neuroimaging, 2010)
INTRODUCTION In the recent years numerous studies have been undertaken to study cerebral perfusion in the surrounding of intracerebral hemorrhage, addressing the question of whether there is a secondary ischemic damage. Most of these studies found a reduced perfusion adjacent to the hematoma. However, the meaning of these findings remains controversial. METHODS We used perfusion computed tomography in 17 patients to study time to peak, cerebral blood flow, and cerebral blood volume as markers of the perihemorrhagic perfusion within 3 hours after symptom onset to search for an early difference between the extent of edema and reduced perfusion. RESULTS All patients showed a significant reduction of all perfusion parameters in the perihemorrhagic area, while there was no difference between the latitude of the reduced perfusion and the edema. CONCLUSION We did not find a difference between the extension of edema and that of restricted perfusion at a very early time point and therefore could not identify any tissue at risk of ischemia. Our findings suggest reduced perfusion and edema to have a common cause rather than presupposing one another.
First published: 14 August 2009
Gesehen am 10.05.2023